Design concept for developing a back pack power mounted harvesting equipment for oil palm - Naik, Ravindra; Annamalai, S.J.K.; Prabinkumar, S.; Prasad, M.V.; Singh, Vidhan (Journal of Plantation Crops, 2013)
-